In control at 50+ : how to succeed in the new world of work - Hannon, Kerry (McGraw Hill, 2022)
"An AARP Work and Jobs Expert provides a road map to success for older workers navigating a post-pandemic workplace When the coronavirus pandemic upended the US economy, many older workers lost their jobs and saw their retirement accounts take a hit. Those who remain employed are grappling with a new way of working: remotely from home, sometimes in isolation, facing daunting technological and social challenges. If you're over 50, this must-have career guide will not only show you how to navigate this new normal, it will empower you to take control of your professional and economic future-with hope, confidence, and optimism. In this book, Kerry Hannon-a leading authority and strategist who has spent three decades covering all aspects of business, careers, personal finance, and retirement-offers advice, guidance, and concrete action steps that will enable older workers to succeed in the workplace and prepare for a financially secure retirement. It features inspiring case studies of how workers over 50 have successfully pivoted and thrived. It identifies the jobs that will be in demand in the post-pandemic economy, as well as leading companies providing new opportunities for older workers in a variety of fields. An essential resource for full-time employees, freelancers, entrepreneurs, and small-business owners alike, In Control at 50+ will show you the way to a brighter professional and financial future"--